Антена на основі фракталу Коха - Сердюк, С. Л. (ХНУРЕ, 2023)
With the development of telecommunications technologies, there are requirements for more compact and modernized antennas. This work is devoted to the study of the antenna based on the Koch fractal. Advantages and examples of using the antenna based on the Koch fractal are given.